2010
DOI: 10.3109/00207450903337721
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Anosmia, Constipation, and Orthostasis and Parkinson's Disease Duration: Results of a Pilot Study

Abstract: Autonomic symptomatology is prevalent in Parkinson's disease (PD) and impacts quality of life, yet little data exist on the presentation of autonomic dysregulation. This study measures orthostasis, constipation, and anosmia in 58 PD patients and 51 age-matched controls enrolled in the University of Florida's Movement Disorders Center. Patients had their blood pressure measured while seated and in standing position, performed the University of Pennsylvania Smell Identification Test (UPSIT), and completed a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
0
11
1
3
Order By: Relevance
“…In undiagnosed individuals, hyposmia is associated with other non-motor PD symptoms, such as constipation [16]. Anosmia and constipation could progress with the primary disease process [17]. However, several researches may indicate that olfactory dysfunction and constipation may do not share the same pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In undiagnosed individuals, hyposmia is associated with other non-motor PD symptoms, such as constipation [16]. Anosmia and constipation could progress with the primary disease process [17]. However, several researches may indicate that olfactory dysfunction and constipation may do not share the same pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Defective smell sense correlates with other modalities in the established phase of PD ; eg, RBD, reduced color vision, constipation, episodic verbal memory, and motor score 29–33. There is also correlation between hyposmia and transcranial ultrasound of the substantia nigra, 123 I‐metaiodobenzylguanidin (MIBG) heart scan, olfactory bulb size, limbic acetylcholinesterase activity, and dopamine transporter imaging 33–38.…”
Section: Olfactionmentioning
confidence: 99%
“…Some cross-sectional studies reveal that diminished scores on olfactoryfunction tests are associated with increased disease duration (167,168), while others do not (22,23,25,117,148,169,170). Some studies have reported associations with more severe disease (22,148,168,169,171,172) but others have not (24,25,117,170,(173)(174)(175), even though hyposmia severity is associated with lower dopamine transporter activity (168). While OD does not always develop in parallel with other non-motor symptoms in either sporadic or monogenic PD (65), resolving whether it does develop in parallel with motor symptoms has implications for management.…”
Section: How Is Od Related To Disease Onset and Progression?mentioning
confidence: 99%